Comparison of Costs of Home and Facility-based Basic Obstetric Care in Rural Bangladesh (Journal of Health, Population and Nutrition, 2010)
This study compared the costs of providing antenatal, delivery and postnatal care in the home and in abasic obstetric facility in rural Bangladesh. The average costs were estimated by interviewing midwivesand from institutional records. The main determinants of cost in each setting were also assessed.The cost of basic obstetric care in the home and in a facility was very similar, although care in the homewas cheaper. Deliveries in the home took more time but this was offset by the capital costs associated withfacility-based care. As use-rates increase, deliveries in a facility will become cheaper. Antenatal and postnatalcare was much cheaper to provide in the facility than in the home. Facility-based delivery care is likely tobe a cheaper and more feasible method for the care provider as demand rises. In settings where skilled attendancerates are very low, home-based care will be cheaper.Key words: Comparative studies; Cost-benefit analysis; Healthcare costs; Maternal health; Obstetric care;BangladeshDOI: 10.3329/jhpn.v28i3.5558J HEALTH POPUL NUTR 2010 Jun;28(3):286-293